Kesejahteraan Subjektif Guru Honorer: Trait dan State Syukur - Anggarani, Fadjri Kirana; Andari, Nabila Putri (UIN Sunan Kalijaga, 2024)
Amid the limitations of honorary teachers regarding welfare demands, it shows that there is still a sense of satisfaction and happiness even though the lack of income is a burden and an obstacle. These feelings indicate subjective well-being which not only influenced by material but also internal dispositions. The study aimed to examine the effect of the gratitude trait on subjective well-being directly or indirectly through the mediation of the gratitude state. Participants are honorary teachers in Surakarta with the required sample size of 122 - 144 people. Measurements were made using the subjective well-being scale, the gratitude trait scale, and the gratitude state scale. The data were tested using path analysis model regression analysis based on the procedure of the Baron & Kenny mediator. The results showed a greater role contribution to the direct effect (βc' = 0.326) of the gratitude trait on subjective well-being than the indirect effect through the mediation of the gratitude state (βab = 0.068). These results provide an overview of the subjective well-being of honorary teachers associated with the gratitude trait and the gratitude state. Di tengah keterbatasan guru honorer terkait tuntutan kesejahteraan menunjukkan masih terdapat rasa puas dan bahagia meskipun kekurangan pendapatan menjadi beban dan hambatan. Perasaan tersebut menunjukkan kesejahteraan subjektif yang bukan hanya dipengaruhi oleh material, melainkan disposisi internal. Tujuan penelitian adalah menguji pengaruh trait syukur terhadap kesejahteraan subjektif secara langsung maupun tidak langsung melalui mediasi state syukur. Partisipan adalah guru honorer di Surakarta dengan besar sampel yang dibutuhkan sebanyak 122 - 144 orang. Pengukuran dilakukan menggunakan skala kesejahteraan subjektif, skala trait syukur, dan skala state syukur. Data diuji dengan analisis regresi model analisis jalur berdasarkan prosedur mediator Baron & Kenny. Hasil penelitian menunjukkan kontribusi peran yang lebih besar pada pengaruh langsung (βc’ =0.326) trait syukur terhadap kesejahteraan subjektif dibandingkan pengaruh tidak langsung melalui mediasi state syukur (βab =0.068). Hasil ini memberikan gambaran kesejahteraan subjektif pada guru honorer yang terkait dengan trait syukur dan state syukur.